2015
DOI: 10.2188/jea.je20140108
|View full text |Cite
|
Sign up to set email alerts
|

Socioeconomic Status and Overweight: A Population-Based Cross-Sectional Study of Japanese Children and Adolescents

Abstract: Background: Socioeconomic status (SES) as a determinant of obesity has received scant attention in Japan. This study examined the association between SES and overweight among Japanese children and adolescents. Methods: Cross-sectional analyses of a representative sample of Japanese children (6-11 years: n = 397) and adolescents (12-18 years: n = 397) were performed, with measured heights and weights from the 2010 National Health and Nutrition Examination Survey and the 2010 Comprehensive Survey of Living Condi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(24 citation statements)
references
References 34 publications
2
21
1
Order By: Relevance
“…34 A recent study in Japan also indicated that living on a low household income during childhood or adolescence was associated with being overweight. 35 Taking measures to support those exposed to adverse childhood circumstances is indispensable as childhood socioeconomic disadvantages are linked to poor health in later life as well as poor educational attainment. 36 It is also necessary to investigate the difference in the prevalence of dementia among different cohorts as changes in life style may have effects on the incidence rate.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…34 A recent study in Japan also indicated that living on a low household income during childhood or adolescence was associated with being overweight. 35 Taking measures to support those exposed to adverse childhood circumstances is indispensable as childhood socioeconomic disadvantages are linked to poor health in later life as well as poor educational attainment. 36 It is also necessary to investigate the difference in the prevalence of dementia among different cohorts as changes in life style may have effects on the incidence rate.…”
Section: Discussionmentioning
confidence: 99%
“…While the relative poverty rate of those aged 65 years or older in Japan has been improving(23.0% in 1985, 21.2% in 2000, and 19.5% in 2015), 32 the child poverty rate in Japan had been increasing for a few decades. A recent study in Japan also indicated that living on a low household income during childhood or adolescence was associated with being overweight 35. Even though children with greater resources might have less healthy behavioural choices (eg, playing computer games frequently and having insufficient physical activity), a survey, conducted in Adachi city, Tokyo, suggested that children with socioeconomic disadvantages were more engaged in video games and had worse health outcomes 34.…”
mentioning
confidence: 99%
“…A comprehensive systematic review has shown low SES to be associated with obesity as early as 1989, yet there is still little consensus on its definition and indicators (62). Rather, different researchers choose different measures and take cues from each other (63)(64)(65)(66). Hence, there was great variation in SES indicators used across our included studies, with five reporting education (28,41,42,54,59), three for income (27,28,43,46,50,51), two for SES quintile (27,37,50,51), and one each for ethnicity (49), parental income (40), parental education (55,56), federal poverty level (57) and employment (59).…”
Section: Effectiveness Of Lifestyle Interventions For the Prevention mentioning
confidence: 99%
“…Childhood overweight and obesity were determined according to the age-and sex-specific BMI cut-off points proposed by the International Obesity Task Force (IOTF) [10]. The cut-off points, which was based on the data including Asian people, have been used in many epidemiological studies for Japanese children and adolescents [11][12][13][14][15]. In the present study, overweight and obesity were combined into the single variable overweight/obesity because the number of participants with obesity was small.…”
Section: Definition Of Overweight/obesity and Central Obesitymentioning
confidence: 99%